2014
DOI: 10.1007/s10565-014-9279-0
|View full text |Cite
|
Sign up to set email alerts
|

Mustard gas surrogate, 2-chloroethyl ethylsulfide (2-CEES), induces centrosome amplification and aneuploidy in human and mouse cells

Abstract: Mustard gas is a simple molecule with a deadly past. First used as a chemical weapon in World War I, its simple formulation has raised concerns over its use by terrorist organizations and unstable governments. Mustard gas is a powerful vesicant and alkylating agent that causes painful blisters on epithelial surfaces and increases the incidence of cancer in those exposed. The mechanism of mustard gas toxicity and tumorigenesis is not well understood but is thought to be mediated by its ability to induce oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It is vital to develop methods or materials to detoxify or remove the chemical warfare agents. 3,4 Sulfur mustard can be detoxied by dehydrohalogenation, hydrolysis or oxidation. Dehydrohalogenation and hydrolysis suffer difficulties due to slow kinetics, the low solubility of sulfur mustard in water and the formation of toxic products.…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to develop methods or materials to detoxify or remove the chemical warfare agents. 3,4 Sulfur mustard can be detoxied by dehydrohalogenation, hydrolysis or oxidation. Dehydrohalogenation and hydrolysis suffer difficulties due to slow kinetics, the low solubility of sulfur mustard in water and the formation of toxic products.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, after cutaneous exposure, SM induced DNA adducts could also be detected systemically in many internal organs, such as brain, lung, kidney, and spleen (Batal et al, 2014). In contrast to bi functional agents, mono functional agents, such as CEES, can only form monoadducts, with N7 ethylthioethyl guanine (N7 ETE Gua) being the most abundant base damage, however still sufficient to induce genomic instability in human cells (Batal et al, 2014;Bennett et al, 2014). In addition, it has been reported that several hours after treatment, mustard agents induce oxidative stress via mitochondrial dysfunction, induction of ROS/RNS generating genes, and GSH depletion on a cellular level or via the recruitment of ROS/RNS generating immune cells on a tissue level, which also leads to the generation of oxidative DNA damage Jain et al, 2011;Steinritz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This should be investigated further as it has important consequences in terms of the ability of SM to induce aneuploidy/mutagenesis/carcinogenesis. Interestingly, a study published during the preparation of this manuscript demonstrated that a monofunctional analogue of SM (2-chloroethyl ethyl sulphide) was able to induce centromere amplification and aneuploidy in human and mouse cells (Bennett et al, 2014). As mentioned earlier, the microarray analysis identified changes in multiple genes involved in cellular replication.…”
Section: Discussionmentioning
confidence: 64%